Physiological responses to hypersalinity correspond to nursery ground usage in two inshore shark species (Mustelus antarcticus and Galeorhinus galeus) - Tunnah, L; MacKellar, SRC; Barnett, DA; MacCormack, TJ; Stehfest, KM; Morash, AJ; Jayson Semmens; Currie, S (2016)
Shark nurseries are susceptible to environmental fluctuations in salinity because of their shallow, coastal nature; however, the physiological impacts on resident elasmobranchs are largely unknown. Gummy sharks ( Mustelus antarcticus ) and school sharks ( Galeorhinus galeus ) use the same Tasmanian estuary as a nursery ground; however, each species has distinct distribution patterns that are coincident with changes in local environmental conditions, such as increases in salinity. We hypothesized that these differences were directly related to differential physiological tolerances to high salinity. To test this hypothesis, we exposed wild, juvenile school and gummy sharks to an environmentally relevant hypersaline (120% SW) event for 48 h. Metabolic rate decreased 20–35% in both species, and gill Na + /K + -ATPase activity was maintained in gummy sharks but decreased 37% in school sharks. We measured plasma ions (Na + , K + , Cl − ) and osmolytes [urea and trimethylamine oxide (TMAO)], and observed a 33% increase in plasma Na + in gummy sharks with hyperosmotic exposure, while school sharks displayed a typical ureosmotic increase in plasma urea (∼20%). With elevated salinity, gill TMAO concentration increased by 42% in school sharks and by 30% in gummy sharks. Indicators of cellular stress (heat shock proteins HSP70, 90 and 110, and ubiquitin) significantly increased in gill and white muscle in both a species- and a tissue-specific manner. Overall, gummy sharks exhibited greater osmotic perturbation and ionic dysregulation and a larger cellular stress response compared with school sharks. Our findings provide physiological correlates to the observed distribution and movement of these shark species in their critical nursery grounds.